Conquest of the tropics / Conquista de los trópicos (1914)
This book is the first of a series planned to describe certain big businesses whose histories and operations concern and should interest the public. The publishers do not wish any one to be deceived into believing that this series is any different from what it pretends to be as now announced. It is planned as an open and above-board presentation frankly puttinforth the interesting points of large business enterprises.